Pengaruh Good Corporate Governance dan Struktur Kepemilikan terhadap Kinerja Perusahaan Sektor Keuangan di Bursa Efek Indonesia - Kemala, Anggun; Syofyan, Efrizal (Jurnal Eksplorasi Akuntansi, 2025)
This study examines the influence of good corporate governance (GCG) and ownership structure on the financial performance of banking and insurance companies listed on the Indonesia Stock Exchange during 2020–2023. GCG is measured by the board of commissioners, board of directors, and audit committee, while ownership structure is represented by managerial and institutional ownership, with Return on Equity (ROE) as the performance indicator. Based on 80 observations from 20 companies and multiple linear regression analysis, the results indicate that the board of directors has a positive and significant effect on financial performance, whereas the board of commissioners, audit committee, managerial ownership, and institutional ownership show no significant effect. These findings imply that strengthening the effectiveness of the board of directors is crucial to enhance profitability, while other GCG mechanisms and ownership structures should be optimized through greater independence of commissioners, stronger audit functions, and more active institutional investor monitoring.